Crhr1 and epinephrine utilize the central Ras-MAPK pathway in mediating the acute stress-related locomotor activity in zebrafish larvae - Khalid, Enezi; Vijayan, Mathilakath M. (Frontiers in Endocrinology, 2025)
IntroductionAlthough the Crh-Crhr1 system is the proximal trigger for the stressor-induced corticosteroid release, its role in initiating the fight-or-flight response to an acute stressor is unclear. We hypothesized that the Crh-Crhr1 system deploys the central Ras-Mapk (mitogen-activated protein kinase) pathway and rapidly increases the locomotor activity in zebrafish larvae.MethodsWe tested this using an acute stressor-induced hyperactivity model in larval zebrafish that is Crhr1-dependent, and a pharmacological inhibitor of Ras (BAY-293). ResultsThe larval hyperactivity response to stress disappeared after pretreatment with BAY-293. Acute CRH exposure stimulated the hyperactivity but at a lower magnitude than epinephrine; however, both responses were inhibited by BAY-293. Immunohistochemical localization revealed rapid phosphorylation of ERK1/2 in the pallium and hypothalamic regions after acute CRH and epinephrine treatment. The lack of Crhr1 (crhr1-/-) upregulated the a1-adrenoceptors (adra1ab and adra1ba) and abolished the epinephrine-induced, but not the forskolin-induced hyperactivity. The acute stressor also increased the transcript abundance of c-fos, commonly used as a marker of neuronal activation and plasticity. This immediate early gene response to stress was mimicked by epinephrine, but not Crh treatment, and was Ras-dependent. The acute stressor- or epinephrine-induced c-fos response was unaltered in larvae lacking a functional Crhr1.DiscussionThis study reveals the activation of the Ras-Mapk pathway by Crhr1 as a central mechanism modulating the acute stress-induced larval hyper-locomotor activity but not the c-fos response in zebrafish. Altogether, our results suggest a complementary but essential role for Crhr1 in facilitating the epinephrine-mediated fight-or-flight response but not the stress-habituation response.